Formulation and Evaluation of Ibuprofen Loaded Lipospheres for Effective Oral Drug Delivery (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Ibuprofen (IBU) is an anti-inflammatory drug characterized by low solubility and bioavailabilty. This study was to develop IBU-liposphere and investigated for in vitro and in vivo performance. IBU free base was incorporated into lipospheres based on micronized beeswax and Phospholipon® 90H in the ratio of (1:3), via hot emulsification. IBU-loaded lipospheres were characterized based on morphology, encapsulation efficiency (EE%), and in vitro drug release. Analgesic, anti-inflammatory activities and the pharmacokinetics were similarly evaluated. Minimum and maximum encapsulation efficiency (EE%) of 89.4 and 97.9% were obtained for lipospheres A1 and A3, respectively. Stable, spherical and smooth lipospheres of size range 101 ± 0.30 to 178 ± 0.30 ?m were obtained. Minimum and maximum release of 75 and 96.9% were obtained for A1 and A3, respectively. Significant (p